Case study: urethral diverticulum with calcifications in a premenopausal woman - Vladimir D. Chuprinin; Anton A. Gorpenko; Nikon V. Zaitsev; Aleksandra V. Asaturova; Natalia A. Buralkina (IP Berlin A.V., 2020)
Female urethral diverticulum is a fairly rare pathology, the frequency of which ranges from 0.02 to 6.00% of women worldwide. The stones inside urethra diverticulum even more rare. The most common reasons of urethral diverticula are frequent bladder catheterizations, labour trauma, infections. Clinically is may present with the dysuria, dyspareunia, dribble, urinary incontinence, vaginal discomfort. Voiding cystourethrography and cystourethroscopy are the most accurate methods of diagnosis for urethral diverticula. The presented article describes the clinical case in women with urethral diverticulum who complained on the vaginal discomfort, dyspareunia and presentation of the brown stones in vagina and underwent surgical excision of diverticulum with urethral reconstruction.